Role of Genetic Testing and Complex Endoscopic Examination in Differential Diagnosis of Hereditary Polyposes in Pediatric and Adolescent Patients: 10 Years Clinical Experience - Tatiana S. Belysheva; Tatiana V. Nasedkina; Timur T. Valiev; Elena V. Sharapova; Vera V. Semenova; Valentina M. Kozlova; Svetlana N. Mikhaylova; Irina S. Kletskaya; Alexey V. Butuzov; Yana V. Vishnevskaja; Valeria V. Lozovaya; Olga A. Gusarova; et al. (Вопросы современной педиатрии)
Background. Hereditary polyposis syndromes (HPS) are a group of rare genetic diseases characterized by multiple epithelial lesions in the gastrointestinal tract (GIT) with high risk of malignancy and neoplasia development in other localizations. The case follow-up tactics in hereditary polyposes have significant differences, and differential diagnosis can be complicated due to the phenotype variability and the clinical manifestations similarity. Objective. The aim of the study is to determine the role of molecular genetic testing and endoscopic examination in the diagnosis and management of children with HPS. Materials and methods. The retrospective observational study included 17 patients with clinical signs of hereditary polyposes who applied to the L.A. Durnov Research Institute of Pediatric Oncology and Hematology during the period from 2013 to 2023. All patients underwent molecular genetic testing and comprehensive endoscopic examination of upper and lower GIT. Results. We have divided patients into 7 groups according to the results of genetic testing. Patients had various mutations in genes associated with hereditary tumor syndromes: STK11 (35.3%; n = 6), APC (17.6%; n = 3), PTEN (11.8%; n = 2), SMAD4 (5.9%; n = 1), BMPR1A (5.9%; n = 1), MUTYH (5.9%; n = 1), MLH1 (5.9%; n = 1). One female patient with colorectal cancer with history of adenomatous polyp had pathogenic variants in the ATM and CHEK2 genes; it could be considered as multi-locus tumor syndrome (MINAS) (5.9%, n = 1). Another female patient (5.9%) had multiple gastric body hamartoma polyps and multiple gastric gastrointestinal stromal tumors (GIST) but with no pathogenic mutations. Complex endoscopic examination was performed in 14 (82.3%) patients. Epithelial or non-epithelial lesions of the stomach and intestine were revealed in all cases. Malignant tumors of duodenum and colon were diagnosed in 3 out of 14 patients (21.4%). Morphological variants of these GIT lesions were represented by hamartoma, hyperplastic, and juvenile polyps, adenomas, serrated adenomas, adenocarcinoma, and GIST. The diagnosed epithelial lesions of the stomach, duodenum, and colon were removed via endoscopic polypectomy and endoscopic mucosal resection in 8 out of 14 patients (57.1%). Some cases required small bowel resection (14.3%, n = 2), total colectomy (14.3%, n = 2), and gastrectomy (14.3%, n = 2). Conclusion. Understanding the molecular and biological etiology of HPS, its endoscopic diagnosis, and treatment features allows us to optimize the management of such patients and to minimize the risks of developing malignant tumors in upper and lower GIT, as well as extraintestinal tumors by carrying out timely medical and preventive measures.